Fatal Spontaneous Intracranial Hemorrhage in the Setting of Rivaroxaban-Associated Thrombocytopenia: Report of Autopsy Findings and Review of the Literature. (21st September 2018) - Yu, Qiqi; Williams, Eliot; Brooks, Erin
Abstract: Introduction: Rivaroxaban, a factor Xa inhibitor, is a novel oral anticoagulant that was approved in 2011 as an alternative to warfarin for stroke prevention in atrial fibrillation. Although thrombocytopenia induced by novel oral anticoagulant therapy in general is reported relatively infrequently, in a recent trial comparing warfarin to rivaroxaban, thrombocytopenia was reported in 3 of 1, 280 patients (0.2%) on rivaroxaban. We report an exceptionally rare case of fatal intracranial hemorrhage caused by acute thrombocytopenia while anticoagulated on rivaroxaban. Case Study: A 72-year-old man, who was on rivaroxaban (20 mg/d) for nonvalvular atrial fibrillation, was admitted to our hospital for sudden-onset left-sided hemiparesis. Cranial imaging revealed intraparenchymal hemorrhage and initial laboratory coagulation parameters showed a platelet count of 5 K/µL with an INR of 1.8; 6 months previously, his platelet levels had been normal. He was treated with platelets, vitamin K, and factor 7. His brain bleeding progressed on imaging despite aggressive blood product replacement. Thromboelastogram was consistent with thrombocytopenia but negative for other coagulation abnormalities. Other possible etiologies for thrombocytopenia were investigated without success. At autopsy, the patient had diffuse cutaneous and mucosal petechial hemorrhage. Neuropathologic examination showed two hemorrhagic foci with one occupying approximately 90% of the right frontoparietal white matter, extending into subarachnoid and subdural spaces, and the other seen in right temporoparietal white matter (2.3 cm). Transtentorial herniation was evident. Discussion: Life-threatening bleeding is very rare in patients on rivaroxaban. Thrombocytopenia during the administration of rivaroxaban, however, can increase the risk of intracranial hemorrhage. Reversal of rivaroxaban in cases of hemorrhage can be challenging; prothrombin complex concentrates may not result in effective hemostasis. Clinicians are advised to carefully monitor platelet levels after initiating rivaroxaban or other novel oral anticoagulant therapy. Autopsy can be an important means of excluding other competing causes of thrombocytopenia/hemorrhage and establishing risk factors.